Translating taste: A linguistic and gastronomic analysis of traditional dish names on menus - Retno Wulandari Setyaningsih; Haru Deliana Dewi; Doni Jaya (Studies in English Language and Education, 2026)
Surabaya has been recognized as one of the best culinary cities in ASEAN according to TasteAtlas 2023/2024, particularly for its traditional dishes and authentic dining establishments. However, various English translations of the same traditional dishes appear across restaurant menus, potentially influencing foreign tourists’ perception of Indonesian cuisine. This study investigates the English usage and gastronomic elements embedded in the translation of traditional dish names on restaurant menus. Drawing on a dataset of 315 traditional dishes and their English translations extracted from 35 menus of four- and five-star hotels in Surabaya, this research applies AntConc software to analyze vocabulary frequency, collocation patterns, keyword distribution, and clusters. The linguistic patterns are examined alongside seven gastronomic elements: ingredients, cooking methods, appearance, flavors, the name of the dish’s creator, geographical origin, and transliteration, to evaluate how informative and persuasive functions are fulfilled. The findings show that the vocabulary used in the translations is relatively limited and repetitive, dominated by nouns denoting ingredients and past participle verbs denoting cooking methods. Six gastronomic elements appear frequently, with transliteration being the least utilized and the creator’s name absent. These results indicate that current translations prioritize informative over persuasive functions. The study suggests that menu translations should be standardized and incorporate gastronomic elements that enhance persuasive appeal to support culinary tourism.